Edukasi Kesehatan Gigi dan Mulut untuk Meningatkan Perilaku Hidup Sehat Anak Usia Sekolah Dasar - Utari Zulkaidah; Arsad Arsad; Yulistina Yulistina; Rezki Dirman; Nasrayanti Nurdin; Suci Qardhawijayanti (Universitas Pahlawan Tuanku Tambusai, 2026)
Dental and oral health problems in elementary school children are still a public health problem, especially in areas with limited access to health services. Low knowledge and behavior of maintaining dental and oral hygiene contributes to the high incidence of dental caries in children. This community service activity aims to increase children's knowledge and healthy living behavior through dental and oral health education. The activity was carried out at SD 4 Lainungan, Pabaraseng Village, Sidenreng Rappang Regency, with the target of elementary school students. The methods used include interactive counseling as well as demonstrations and good and correct brushing practices. Evaluation was carried out through questions and answers and observation of toothbrushing skills. The results of the activity showed that most of the students had low knowledge and many experienced dental caries. After educational activities, there was an increase in students' understanding and skills in maintaining dental and oral health. Education accompanied by direct practice is effective as a promotive and preventive effort in shaping children's healthy living behaviors.